B2B: Prostate Cancer Summary - Stacy Loeb, Peter C. Black, Alexander W. Wyatt, Yaw A. Nyame, Neal Shore, Derya Tilki, Elena Castro, Matthew Cooperberg, Veda Giri, Maria J. Ribal, Giovanni Lughezzani, Rafael Sánchez-Salas, Caroline M. Moore, Art Rastinehad, Linda Kerkmeijer, Hashim U. Ahmed, Shusuke Akamatsu, Alexandre de la Taille, Martin Gleave, Simon Tanguay (Société Internationale d’Urologie Journal)
None.